2017
DOI: 10.24221/jeap.2.3.2017.1407.330-340
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de geração de energia eólica no Submédio São Francisco

Abstract: A B S T R A C TThe major potential of wind power generation in the world and a possibility of electric energy production make it an alternative source to increase the diversity in the world energy matrix. The objective was to characterize a predominant velocity and direction of the wind for generation of wind power in the Submédio São ) of the São Francisco Submiddle. The highest values of wind power are highlighted for the municipalities of Dormentes, Lagoa Grande, Curaçá, Petrolina, Afrânio, Pedro Alexandre,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(8 reference statements)
0
1
0
3
Order By: Relevance
“…By observing the average monthly variation of wind direction for ve regions of the Paraíba state (São Gonçalo, Monteiro, Patos, Campina Grande and João Pessoa), found similar results to those found here, with wind direction in the regions varying between the angles of 20º and 180° in the study period. In an analogous study for the Sub-middle São Francisco River,Lopes et al (2017) found a predominant frequency in the southeast direction for the winds in the region.…”
mentioning
confidence: 81%
“…By observing the average monthly variation of wind direction for ve regions of the Paraíba state (São Gonçalo, Monteiro, Patos, Campina Grande and João Pessoa), found similar results to those found here, with wind direction in the regions varying between the angles of 20º and 180° in the study period. In an analogous study for the Sub-middle São Francisco River,Lopes et al (2017) found a predominant frequency in the southeast direction for the winds in the region.…”
mentioning
confidence: 81%
“…A região segundo classificação climática de Peel et al ( 2007) apresenta clima BSh, predominando o semiárido, com precipitação média anual aproximada de 430 mm. A umidade relativa do ar média anual é de 66% e a temperatura média anual do ar é de 26,5ºC (Pinheiro et al, 2015;Nemus, 2016;Sá, 2016;Lopes et al, 2017;Silva et al, 2021). Figura 1.…”
Section: Caracterização Da áRea De Estudounclassified
“…A umidade relativa do ar média anual é de 66% e a temperatura média anual do ar de 26,5 ºC. A evapotranspiração potencial média anual é de 1550 mm (Pinheiro et al, 2015;Lopes et al, 2017;CODEVASF, 2019).…”
Section: áRea De Estudounclassified